Exploring mRNA vaccines: an immunology case-study approach that leverages team-based learning in an integrated intermediate-level biology course - Nannas, Natalie J.; Chang, Wei-Jen; Datta, Rhea R.; McDaniels, Nicole L.; Bochkov, Ivan D.; Relles, Noelle J. (Frontiers in Education, 2025)
The American Association for the Advancement of Science (AAAS)’s call to action outlined a vision for the future of undergraduate biology education which included core concepts and inquiry-based skills to engage students in understanding the natural world. The report highlighted the need to connect the classroom to the real world to promote science literacy. Immunology is a field that connects AAAS-identified core concepts to the real world, however there has been a lack of emphasis on immunology education, contributing to low levels of immune literacy in the general public and subsequent vaccine hesitancy. The undergraduate course Genes, Molecules, and Cells (BIO211) at Hamilton College seeks to fill this gap by preparing students early in their undergraduate education with the necessary foundations in biochemistry, cell biology, molecular biology and genetics for studying immunology in the context of the SARS-CoV2 pandemic and subsequent mRNA vaccine development. Importantly, the course deviates from the traditional pathway of teaching the central dogma, beginning instead with translation and following the story of mRNA delivery to cells and production of the spike protein. The lecture includes traditional lecture-style teaching, combined with case studies and team-based learning to enhance student learning and engagement with the material. The lecture and its associated laboratory successfully address all six core competencies of the ImmunoSkills Guide. Pairing partners for a final poster presentation on debunking vaccine misinformation or a novel use of mRNA technology helps students make the connection between science and society while working collaboratively to communicate scientific concepts to a broad audience. After four semesters of this course, students consistently showed statistically significant improvement on the Molecular Biology Capstone Assessment. Students reported that iterative, low-stakes team questions were highly effective tools for learning, leading to high levels of self-reported participation and engagement, but were less enthusiastic about the benefits of the collaborative group format. On the end-of-semester poster project students reported high enthusiasm and effectiveness. Future goals of the course include more closely tying the relevance of laboratory modules to lecture case studies and improving the experience of team-based lecture questions.